Nilai-Nilai Pendidikan Dalam Shalat Fardhu Menurut Kajian Kitab Mabadi’ul Fiqhiyah - Dini Gita Sartika; Ayu Lestari; Zahara Tulhusni; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2023)
The book Mabadi'ul Fiqhiyah is one of the books belonging to the Imam Syafi'i school of thought, which is one of the schools of thought that most or the majority of Indonesian people use to this day. His work Umar Abdul Jabbar is divided into four juz and he first wrote this book in the month of Rajab in 1932 AD/1353 H. This Mabadi'ul Fiqhiyah book explains or contains related Islamic religious laws. with daily worship practices. The aim of this research is first, namely to find out what values ​​are contained in prayer according to the study of the Mabadi'ul Fiqhiyah book, secondly, namely to find out the application of values ​​in prayer according to the study of the Mabadi'ul Fiqhiyah book. Research shows that the values ​​of prayer in the book mabadiul fiqhiyah are getting closer to Allah SWT, reassuring the soul, educating time discipline, educating obedience and order, maintaining cleanliness. The values ​​of the prayer service in the Mabadiul Fiqhiyah book are a means to perfect the prayer service and are a medium to get closer to Allah SWT.